2017
DOI: 10.1016/j.joca.2017.02.790
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow lesions on magnetic resonance imaging in hand osteoarthritis are associated with pain and interact with synovitis

Abstract: In hand OA patients severe synovitis is associated with joint pain, which is worsened when BMLs co-occur, suggesting synovitis as primary target of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 19 publications
(19 reference statements)
3
27
2
4
Order By: Relevance
“…[H2] Advances in ultrasonography and MRI In the past 10 years, the use of ultrasonography and MRI for assessing patients with hand OA has increased, providing greater insight into the pathology of the disease and increased evidence that these imaging modalites have a higher sensitivity than radiography in determining the presence of pathological features such as osteophytes, JSN and central erosions 76,77,78,79,80,47 . Using ultrasonography and MRI, researchers have shown that inflammatory changes in the synovium and at the enthesis of the hands are a common finding in hand OA 81,82,83 .…”
Section: [H1] Imagingmentioning
confidence: 99%
“…[H2] Advances in ultrasonography and MRI In the past 10 years, the use of ultrasonography and MRI for assessing patients with hand OA has increased, providing greater insight into the pathology of the disease and increased evidence that these imaging modalites have a higher sensitivity than radiography in determining the presence of pathological features such as osteophytes, JSN and central erosions 76,77,78,79,80,47 . Using ultrasonography and MRI, researchers have shown that inflammatory changes in the synovium and at the enthesis of the hands are a common finding in hand OA 81,82,83 .…”
Section: [H1] Imagingmentioning
confidence: 99%
“…The mean age for all studies was 64.4 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Most studies (n = 13) were performed on both genders, although the majority of the subjects in each study were female.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only two studies [26,32] had female subjects only and one study did not report the gender of the participants [25]. Of these studies, 13 were from observational cohort studies: the Hand OSTeoarthritis in secondary care (HOSTAS) [27,[29][30][31] the Oslo hand OA cohort [18-23, 25, 32] and a clinical trial: the digital osteoarthritis in refractory hand OA (DORA) study [28]. All articles examined BMLs and various subchondral features using MRI.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations